(untitled) (Damu Journal of Sport Sciences, 2025)
This study aims to analyze the performance level of the players of the three winning teams in the 23rd Arab Men's Volleyball Championship, held in the Kingdom of Bahrain in late 2024, and its relationship to the final ranking of these teams. The research problem was to identify the strengths that contributed to achieving the top positions, as well as to determine the reasons that led to the teams losing points or sets. The most important objective of the research was to present a scientific analysis of the level of effectiveness of Arab players' performance, contributing to the development of training methods by identifying the skills that most influence match results. This study seeks to evaluate the effectiveness of the players' technical and skill performance in general in this tournament, in which eight teams participated, and its relationship to their rankings. The research procedures consisted of choosing a descriptive study methodology using a survey method. The study relied on the methodology Quantitative and descriptive analysis of players' technical or skill performance was conducted by collecting statistical data from matches and analyzing it using sports performance analysis software. A questionnaire was prepared to select the most important skills that influence points. From the results of the statistical analysis, the researchers concluded that there is a strong correlation between the overall skill performance efficiency and the final ranking of the teams. The researcher recommended the adoption of digital performance analysis to periodically evaluate the performance of players and teams, and to increase participation in high-level international tournaments to raise the level of exposure and benefit from advanced schools in the game.